The decreased competition in expanding versus mature juniper woodlands is counteracted by adverse climatic effects on growth - Gimeno, Teresa E.; Pías, Beatriz; Martínez-Fernández, Jesús; Quiroga, David L.; Escudero, Adrián; Valladares, Fernando (European Journal of Forest Research, 2011)
World-wide deforestation is being reversed in Mediterranean continental areas, where abandonment of traditional practises favours the expansion of valuable habitats, like Juniperus thurifera woodlands. We hypothesised that pre-existing trees facilitate establishment in expanding woodlands, whereas in mature woodlands, competition leads to patch disaggregation. We compared the imprint of these processes on growth, demographic and spatial structure of expanding and mature J. thurifera woodlands. We selected plots where we geopositioned, aged and quantiﬁed the morphological characteristics of all trees. In the mature woodland, trees arranged in clumps and randomly in the expanding woodland. Competition negatively affected growth, was greater in the mature woodland and led to disaggregation of juvenile clumps. Differences in growth between the mature and the expanding woodland disappeared in climatically unfavourable years, suggesting that adverse climate constrains growth more in expanding than in mature woodlands. We suggest that change in the dispersal agents and a decrease of facilitation underlay differences in spatial patters between the expanding and the mature woodland. Observed effective recruitment in less than 30 years into the expanding woodland evidenced that propagule arrival and sapling survival do not constrain woodland expansion. Furthermore, growth of juveniles established in these new areas is favoured by reduced intraspeciﬁc competition. However, we expect growth in expanding woodlands to be negatively impacted by climate change. We conclude that under current global change scenario, conservation of J. thurifera woodlands is favoured by changes in land use, but greater frequency and severity of drier than usual episodes could hamper natural reforestation.
Keywords: Juniperus thurifera; Plant–plant interactions; Radial growth; Spatial pattern; Woodland expansion; Woodlandisation

Asociación espacial de especies leñosas dominantes a lo largo de gradientes ambientales: estudio de la regeneración de un bosque mediterráneo continental - Granda, Elena; Valladares, Fernando; Escudero, Adrián; de la Cruz, Marcelino; Gimeno, Teresa E; Matesanz, Silvia; Pías, Beatriz; López, David (V Congreso Forestal Español, 2009)
Los fenómenos de competencia y facilitación entre plantas presentan importantes variaciones según la etapa de vida y fisiología de las especies que interactúan, dependiendo además del estrés abiótico e interacciones indirectas. Dada la importancia del análisis espacial en el entendimiento de la estructura y funcionamiento de los ecosistemas, hemos llevado a cabo un estudio descriptivo en localidades contrastadas de bosque mediterráneo continental en el Parque Natural del Alto Tajo (Guadalajara). Se ha registrado el clima de cada localidad y los patrones espaciales de individuos de las cuatro especies dominantes (Quercus ilex subsp. ballota, Quercus faginea, Pinus nigra subsp. salzmannii y Juniperus thurifera). Los propósitos son: determinar patrones de agregación, repulsión o distribución al azar; establecer si dicha distribución está relacionada espacialmente con las características de cada localidad e identificar si los patrones muestran diferencias entre especies. Los resultados indican grandes diferencias entre las cuatro especies. Encontramos que en conjunto, la frecuencia de juveniles era mayor bajo la protección de otros individuos, existiendo diferencias según las especies beneficiarias y benefactoras, y tipo de bosque considerado. Las explicaciones varían desde la facilitación mediada por la mejora en las condiciones microclimáticas hasta una interacción positiva debida al efecto percha o protección frente a los herbívoros. Se discuten las implicaciones de estos resultados para la regeneración natural.
Keywords: Interacciones; Juniperus thurifera L.; Pinus nigra J.F.Arnold subsp. salzmannii (Dunal) F; Quercus faginea Lam.; Quercus ilex subsp. ballota (Desf) Samp.; reclutamiento

Plasticity and stress tolerance override local adaptation in the responses of Mediterranean holm oak seedlings to drought and cold - Gimeno, Teresa E; Pías, Beatriz; Lemos-Filho, José P; Valladares, Fernando (Tree Physiology, 2009)
Plant populations of widely distributed species experience a broad range of environmental conditions that can be faced by phenotypic plasticity or ecotypic differentiation and local adaptation. The strategy chosen will determine a population’s ability to respond to climate change. To explore this, we grew Quercus ilex (L.) seedlings from acorns collected at six selected populations from climatically contrasting localities and evaluated their response to drought and late season cold events. Maximum photosynthetic rate (Amax), instantaneous water use efficiency (iWUE), and thermal tolerance to freeze and heat (estimated from chlorophyll fluorescence versus temperature curves) were measured in 5-month-old seedlings in control (no stress), drought (water-stressed), and cold (low suboptimal temperature) conditions. The observed responses were similar for the six populations: drought decreased Amax and increased iWUE, and cold reduced Amax and iWUE. All the seedlings maintained photosynthetic activity under adverse conditions (drought and cold), and rapidly increased their iWUE by closing stomata when exposed to drought. Heat and freeze tolerances were similarly high for seedlings from all the populations, and they were significantly increased by drought and cold, respectively; and were positively related to each other. Differences in seedling performance across populations were primarily induced by maternal effects mediated by seed size and to a lesser extent by idiosyncratic physiologic responses to drought and low temperatures. Tolerance to multiple stresses together with the capacity to physiologically acclimate to heat waves and cold snaps may allow Q. ilex to cope with the increasingly stressful conditions imposed by climate change. Lack of evidence of physiologic seedling adaptation to local climate may reflect opposing selection pressures to complex, multidimensional environmental conditions operating within the distribution range of this species.
10.1093/treephys/tpn007
Keywords: Adaptation; Biological; Biological: physiology; Cold Temperature; Droughts; eﬃciency; Freezing; Genetic Variation; Hot Temperature; Nuts; photosynthesis; Photosynthesis: physiology; Physiological; Quercus; Quercus ilex; Quercus: physiology; Stress; thermal tolerance; Trees; water; water use; Water: physiology